Klinična uporaba probiotikov v pediatriji - Mičetić-Turk, Dušanka (Zdravniški vestnik, 2011)
The use of probiotics, which was until recently a part of the alternative medicine context, is nowadays a "medical hit". Proof that intestinal microflora is an important part of the intestinal immune and non-immune system represents the basic context of probiotics. These are living microorganisms added to food in sufficient amount for improving intestinal flora and favourably influencing health. The most important mechanisms of probiotic activity are synthesis of antimicrobial agents, use of nutrients necessary for growth of pathogenic flora, inhibition of pathogenic bacterial adhesion, toxins and toxin receptors modification, activation of the immune system by increasing immunoglobulin secretion and cytokine production (interleukin-10 and transforming growth factor-TGF), and decreasing the production of cytokines, tumor necrotizing factor-TNF-a, interferon, and others. Numerous studies in paediatrics have been conducted in the last 20 years with the purpose to define the role of probiotics in different diseases-their use in the prevention and treatment of acute and chronic gastrointestinal diseases as well as of other diseases and disorders, such as atopies, respiratory infections, and others. The use of probiotics is generally estimated as safe since the used microorganisms are the same as those found in the digestive system of a healthy person. In paediatrics the most intense research on probiotics has been performed in treating acute gastroenetrocolitis where their positive effect has already been proved. There are only few studies confirming the effect of probiotics in other gastrointestinal diseases although the results are promising. The research was focused on a few probiotic strains only and therefore the results can not be generalized. The purpose of the article is to present the current state of probiotic use and their effectiveness in gastrointestinal and certain non-gastrointestinal disorders in childhood.
Keywords: črevesne bolezni; Gastrointestinal Diseases; Gastrointestinalne bolezni; immunology; Imunologija; Pediatrics; Pediatrija; Probiotics; Probiotiki; therapy; Zdravljenje